2013
DOI: 10.1371/journal.pone.0083194
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Upregulation of Melanin-Concentrating Hormone in TNBS-Induced Enterocolitis in Adult Zebrafish

Abstract: BackgroundMelanin-concentrating hormone (MCH), an evolutionarily conserved appetite-regulating neuropeptide, has been recently implicated in the pathogenesis of inflammatory bowel disease (IBD). Expression of MCH is upregulated in inflamed intestinal mucosa in humans with colitis and MCH-deficient mice treated with trinitrobenzene-sulfonic acid (TNBS) develop an attenuated form of colitis compared to wild type animals. Zebrafish have emerged as a new animal model of IBD, although the majority of the reported s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 48 publications
8
29
1
Order By: Relevance
“…However, the mortality observed in the TNBS-treated zebrafish in the present study was slightly lower than previously reported by Geiger et al [10], studying a comparable zebrafish model. Brugman et al [6] did not note reduced survival rates in adult zebrafish exposed to a low concentration (0.2%) oxazolone which is lower that the concentration (0.6%) used in this study.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…However, the mortality observed in the TNBS-treated zebrafish in the present study was slightly lower than previously reported by Geiger et al [10], studying a comparable zebrafish model. Brugman et al [6] did not note reduced survival rates in adult zebrafish exposed to a low concentration (0.2%) oxazolone which is lower that the concentration (0.6%) used in this study.…”
Section: Discussioncontrasting
confidence: 74%
“…In this study, transcript levels of IL-1β and TNF-α were significantly elevated in both colitis-groups. Previous zebrafish-based studies have reported an increase in gene expression of IL-1β and TNF-α in adult fish few hours after they had been exposed to oxazolone [6] or TNBS [10]. Similar increases have been reported using larval TNBS-models and qPCR/immunofluorescence techniques [7] [9] [11].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…A second model of intestinal inflammation in adult zebrafish used 2,4,6-trinitrobenzenesulfonic acid (TNBS) in a 30% ethanol solution injected intrarectally [48] . In mice, this model is widely used to study IBD because of clinical and histopathological findings resembling those seen in CD [49,50] .…”
Section: Chemically Induced Adult Modelsmentioning
confidence: 99%